Configurational comparative methods qualitative comparative analysis (QCA) and related techniques - Ragin, Charles C.; Rihoux, Benoit (Thousand Oaks, Calif. ; London : SAGE, 2009)
Provides details on a specific approach to research. The book is relevant to a broad range of disciplines, can be used in teaching and by practitioners, and is focused on an integrated approach to qualitative and quantitative research.
Includes bibliographical references and index.
Specialized.
Description based on print version record.
Keywords: Social sciences -- Comparative method; Social sciences -- Research -- Methodology; Social sciences. -- Comparative method; Social sciences. -- Research. -- Methodology